2017
DOI: 10.3390/nu9050510
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Dietary Calcium Intake on Esophageal Cancer Risk: A Meta-Analysis of Observational Studies

Abstract: Although several epidemiological studies have investigated the association between dietary calcium intake and the risk of esophageal cancer, the results are inconsistent. This study aimed to make a comprehensive evaluation regarding the association between calcium intake and risk of esophageal cancer through a meta-analysis approach. We searched for all relevant articles from the inception to April 2017, using PUBMED, EMBASE, and Web of Knowledge. The pooled odds ratio (ORs) with the 95% confidence interval (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Our findings also revealed that fried food consumption was significantly associated with gastritis problem in Ramadan. These findings were supported by several prior studies 24,25 . Maliha suggested avoiding fried, greasy, and acidic meals during Ramadan to keep away peptic ulcers 26 .…”
Section: Discussionsupporting
confidence: 78%
“…Our findings also revealed that fried food consumption was significantly associated with gastritis problem in Ramadan. These findings were supported by several prior studies 24,25 . Maliha suggested avoiding fried, greasy, and acidic meals during Ramadan to keep away peptic ulcers 26 .…”
Section: Discussionsupporting
confidence: 78%
“…Among dietary factors, an inverse association was reported between dietary vitamin C and vitamin A intake and risk of glioma (Lv et al, 2015;Zhou et al, 2015). Dietary calcium intake has been reported to play a role in the incidence of several cancers (Huncharek et al, 2008;Hidayat et al, 2016;Li et al, 2017;Song et al, 2017). With regard to brain tumors, dietary calcium intake has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous mice study also suggested that dietary intake rich in calcium could help to reduce colon cancer (48). A recent meta-analysis study indicated that higher dietary calcium intake could lower esophageal cancer risks (9). The latest study found that snails contain CaCO 3 crystals in their shell with diverse shell surface functional groups (Figure 1) (8).…”
Section: Discussionmentioning
confidence: 98%
“…Calcium carbonate constitutes 87-96% of the total weight of freshwater snail shells (8). High dietary calcium intake is clinically protective against multiple chronic diseases, including lowering the risks of developing cancer (9,10). Calcium carbonate is also the primary material used to synthesize hydroxyapatite, a biocompatible material with high binding activity to proteins and genetic materials.…”
Section: Introductionmentioning
confidence: 99%